Optimalisasi Komunikasi Metode Situation, Background, Assessment, and Recommendation (SBAR) dalam Serah Terima Perawat - Situmeang, Widiya Yulian; Handiyani, Hanny; Pujasari, Hening; Afriani, Tuti; Nasri, Khairul (Journal of Telenursing (JOTING), 2023)
This study aims to optimize the communication of the SBAR method in nurse handover that encourages a culture of patient safety and effective communication. The method used is a pilot study starting from the process of identification, analysis, prioritization of problems, plan of action, implementation, evaluation, and follow-up plan. The results showed that the application of guidelines and Standard Operating Procedures (SPO) with socialization and handover assistance with SBAR method communication had a good effect, as evidenced by the trial application of the guidelines obtained data there was an increase in the percentage of vital sign mentions of 100%, the results of the latest nursing assessment increased to 40%, the delivery of nursing diagnoses and recommendations for further nursing actions by 60%. The hospital organization is in a stage of movement change where after implementation, the Nursing Services Department and the head of the room try to maintain its sustainability and make the organizational culture in the hospital. In conclusion, the activities that have been carried out during the socialization and mentoring process provide a change in behavior and a good mindset for nurses in implementing and cultivating the implementation of handover with SBAR communication in order to realize quality nursing services. Keywords: Communication, SBAR Method, Handover